A Social Portrait of People with Disabilities in Ireland - WATSON, DOROTHY (Department of Social Protection and ESRI, 2011)
This report ? A Social Portrait of People with Disabilities in Ireland ? examines the circumstances of people with disabilities in Ireland. It is one of a series of Social Portraits on vulnerable groups in Ireland commissioned by the Social Inclusion Division of the Department of Social Protection, from the ESRI. The report draws on a number of sources, primarily the first and second reports from the National Disability Survey (Central Statistics Office, 2008 and 2010). For the first time in Ireland, the National Disability Survey facilitates estimation of the prevalence of disability in the population and also provides the basis for a detailed analysis of the living circumstances and needs of people with disabilities. The concept of disability that underlies this social profile is the `biopsychosocial model? of disability advocated by the World Health Organisation. In this model, disability is understood in terms of how the individual interacts with the physical and social environment. In other words, in order to understand what people are able to do, we need to take account of the resources available to them and the barriers placed before them in their environment as well as their own physical, mental and emotional resources. Therefore, in this report ? as well as examining the number of people with disability and the impact their disability has on them ? we consider their experiences in the educational system and labour market, their social participation and social support and the physical environment and transport.
PUBLISHED
Dublin
Keywords: Social Policy; Disability; Ireland